Use of dermatoglyphic parameters of the medium and proximal phalanges of fingers for integrated legal-medical identification of a person - Yu.Z. Kotsiubynska; N.M. Kozan (Medičnì Perspektivi)
The aim of the study is to search for the possibilities of forensic identification criteria through integrated study of the nature of correlative relationships between the dermatoglyphic parameters of the middle and proximal phalanges of the fingers together with gender and ethno-territorial belonging of persons and identify factor criteria for the diagnosis of unknown person’s phenotype. The material for the study was dermatoglyphs of middle and proximal phalanges of fingers of 480 persons belonging to males and females of different ethno-territorial groups of the Carpathian region, obtained digitally using the Futronic's FS 80 USB 2.0 optical scanner and reformatted from bitmaps to vector graphic objects using algorithm VeriFinger 6.6/Mega Matcher 4.4 Identification Technology Algorithm. The results of quantitative and qualitative study of the morphological elements of dermatoglyphic parameters were subjected to one- and multivariate statistical analysis. Significant differences were found between in incidence of dermatoglyphic parameters in the males and females of the Boiko, Lemko, Hutsul, Opillia, Pokuttia and control groups during the study. On the basis of the obtained result, diagnostic phenotypic complexes of dermatoglyphic parameters of middle and proximal phalanges of the fingers of representatives of different ethno-territorial groups of the Carpathian region were formed, and thus the register of identification criteria was expanded, which can be further used as a separate self-sufficient identification system, as well as together with dermatoglyphic parameters of hands and feet in complex identification expertise.